Nightmare frequency and nightmare distress: Socio-demographic and personality factors - Schredl, Michael; Goeritz, Anja S. (Sleep Science, 2019)
The diagnosis of a nightmare disorder is based on clinically significant distress caused by the nightmares, e.g., sleep or mood disturbances. In order to understand nightmare etiology better empirical research should focus on studying factors that affect nightmare distress in addition to nightmare frequency. Overall, 2492 persons (1437 woman, 1055 men) completed the online survey. Nightmare frequency, global nightmare distress, and personality traits were measured. The findings indicate that in addition to nightmare frequency heightened emotional reactivity measured as neuroticism contribute to global nightmare distress and, thus, supporting the neurocognitive model of Levin and Nielsen (2007). Moreover, the recurring nightmares that relate to a waking-life event were associated with higher nightmare distress. From a clinical viewpoint, it would be desirable to carry out similar surveys using diagnostic interviews in order to determine the presence of a nightmare disorder and study the variables that are related to that diagnosis.
Keywords: Nightmares; Sleep Disorders; Neuroticism; Mood Disorders; Surveys and Questionnaires